Targeting the interleukin‐11 receptor α in metastatic prostate cancer: A first‐in‐man study. Issue 14 (1st April 2015) - Pasqualini, Renata; Millikan, Randall E.; Christianson, Dawn R.; Cardó‐Vila, Marina; Driessen, Wouter H. P.; Giordano, Ricardo J.; Hajitou, Amin; Hoang, Anh G.; Wen, Sijin; Barnhart, Kirstin F.; Baze, Wallace B.; Marcott, Valerie D.; et al.
<x xml:space="preserve">Abstract</x> BACKGROUND Receptors in tumor blood vessels are attractive targets for ligand‐directed drug discovery and development. The authors have worked systematically to map human endothelial receptors ("vascular zip codes") within tumors through direct peptide library selection in cancer patients. Previously, they selected a ligand‐binding motif to the interleukin‐11 receptor alpha (IL‐11Rα) in the human vasculature. METHODS The authors generated a ligand‐directed, peptidomimetic drug (bone metastasis‐targeting peptidomimetic‐11 [BMTP‐11]) for IL‐11Rα–based human tumor vascular targeting. Preclinical studies (efficacy/toxicity) included evaluating BMTP‐11 in prostate cancer xenograft models, drug localization, targeted apoptotic effects, pharmacokinetic/pharmacodynamic analyses, and dose‐range determination, including formal (good laboratory practice) toxicity across rodent and nonhuman primate species. The initial BMTP‐11 clinical development also is reported based on a single‐institution, open‐label, first‐in‐class, first‐in‐man trial (National Clinical Trials number NCT00872157) in patients with metastatic, castrate‐resistant prostate cancer. RESULTS BMTP‐11 was preclinically promising and, thus, was chosen for clinical development in patients. Limited numbers of patients who had castrate‐resistant prostate cancer with osteoblastic bone metastases were enrolled into a phase 0 trial with biology‐driven endpoints. The authors demonstrated biopsy‐verified localization of BMTP‐11 to tumors in the bone marrow and drug‐induced apoptosis in all patients. Moreover, the maximum tolerated dose was identified on a weekly schedule (20‐30 mg/m2). Finally, a renal dose‐limiting toxicity was determined, namely, dose‐dependent, reversible nephrotoxicity with proteinuria and casts involving increased serum creatinine. CONCLUSIONS These biologic endpoints establish BMTP‐11 as a targeted drug candidate in metastatic, castrate‐resistant prostate cancer. Within a larger discovery context, the current findings indicate that functional tumor vascular ligand‐receptor targeting systems may be identified through direct combinatorial selection of peptide libraries in cancer patients. Cancer 2015;121:2411–2421. © 2015 American Cancer Society.